The Taoist body - Schipper, Kristofer Marinus; Duval, Karen C.; Girardot, Norman (Selangor, Malaysia Pelanduk Publications (M) Sdn. Bhd., 1996)
This elegant and lucid introduction to the traditions of Taoism and the masters who transmit them will reward all those interested in China and in religions.
Foreword / Norman Giradot -- 1. Taoism. The Notion of Religion. The Tao. The History of Taoism. The Destruction of Taoism -- 2. Everyday Religion. The Temples. The Calendar. Festivals. Food -- 3. Divinity. Cosmology. The Gods. Spiritual Power -- 4. The Masters of the Gods. Puppets and Mediums. The Barefoot Master and His Ritual. The Dignitaries of the Tao. The Register -- 5. Ritual. Becoming a Tao-shih. The Sacrifice of Writings. The Altar -- 6. The Inner Landscape. The Environment. The Image of the Body. The Inhabitants -- 7. Lao Tzu, the Body of the Tao. Birth -- 8. Keeping the One. The Preliminary Stage: The Work of the Chi (Chi-kung). Chaos: The Work of the Tao. The Return -- 9. The Immortals. The Abstinence from Grains. Mountains. Alchemy -- 10. Teaching without Words. The Kingdom of Humpty-Dumpty. The Fast of the Heart. Daily Life.
Translation of: Le corps taoïste.
Includes bibliographical references (pages 249-261) and index.
Keywords: Taoism